EDMed Inconel 718 using powder metallurgy (P/M) sintered electrode made with nano and micron sized powders - Subrahmanyam, Rallabhandi Venkata Surya; Koona, Ramji; Pujari, Srinivasa Rao (2020)
This work presents experimental data carried out for surface modification of Inconel 718 using WC/Cu composite powder metallurgy (P/M) electrodes made of nano and micron sized particles. Both machine and tool parameters were selected for study and experiments were planned as per Taguchi’s L18 mixed orthogonal array in order to find the influence of parameters on surface roughness (SR) and micro-hardness (MH). Peak current, particle size and pulse on time were found to be most significant on both SR and MH. High reactive surface area of nano particles made surface alloying greater than the other tool electrodes and has shown its influence positively on both SR and MH. The EDX analysis reveals the migration of WC and Cu elements and deposition of carbon and oxygen particles on the surface. The XRD spectrum confirms presence of carbides (WC, W2C, Fe5C2, Cr7C3, Fe7C3 and Fe3C), oxides (Fe3O4, WO3 and Cr3O) and other intermetallics at different machining conditions indicating the influence of Pulse on time (TON) and Peak current (IP) on discharge energies and in turn on the properties of machined surface. The carbides generated on the machined surface increased the hardness to 845HV without much sacrifice of the roughness of the machined surface. The range of roughness values obtained in the present investigation is 2.443 to 4.098µm.
Bibliografija: 29 jed.
Abstract.
Keywords: Metalurgija praha -- Kompoziti -- Hrapavost površine -- Elektrode -- Mikrotvrdoća